Marketing Adoption Among Small and Medium Scale Malay Entrepreneurs in Peninsular Malaysia - Yacob, Nik Rahimah (The International Journal of Accounting and Business Society, 1996)
This study exmines the influence of external, internal and organization factors on marketing adoption among small and medium scale Maly entrepreneurs in Peninsular Malaysia. Marketing Adoption was operatio